Clinical outcome of patients with ST‐elevation myocardial infarction and angiographic evidence of coronary artery ectasia. Issue 2 (5th May 2021) - Baldi, Cesare; Silverio, Angelo; Esposito, Luca; Di Maio, Marco; Tarantino, Fabio; De Angelis, Elena; Fierro, Giuseppe; Attisano, Tiziana; Di Muro, Michele Roberto; Maione, Antongiulio; Pierri, Adele; Vigorito, Francesco; et al.
Abstract: Objectives: The aim of this study was to describe the prevalence of coronary artery ectasia (CAE) in patients with ST‐elevation myocardial infarction (STEMI) and to compare the long‐term outcome of subjects with and without CAE undergoing emergent coronary angiography. Background: The prognostic impact of CAE in STEMI patients has been poorly investigated. Methods: This retrospective, single‐center, study included consecutive patients with STEMI undergoing emergent coronary angiography from January 2012 to December 2017. The primary endpoint was the assessment of recurrent myocardial infarction (MI) in patients with versus those without CAE at the longest available follow‐up. The propensity score weighting technique was employed to account for potential selection bias between groups. Results: From 1, 674 patients with STEMI, 154 (9.2%) had an angiographic evidence of CAE; 380 patients were included in the no CAE group. CAE patients were more often males and smokers, and showed a lower prevalence of diabetes than no CAE patients. After percutaneous coronary intervention, the corrected thrombolysis in MI frame count ( p  < .001) and the myocardial blush grade ( p  < .001) were significantly lower in CAE than in no CAE patients. The mean follow‐up was 1, 218.3 ± 574.8 days. The adjusted risk for the primary outcome resulted significantly higher in patients with CAE compared to those without (adjusted HR: 1.84; p = .017). No differences in terms of all‐cause and cardiac death were found between groups. Conclusions: In this study, STEMI patients with CAE had a distinct clinical and angiographic profile, and showed a significantly higher risk of recurrent MI than those without CAE.